Dark soliton array generation using fiber loop and ring resonators - Kusirirat, Kathawut (The Optical Society, 2010)
We propose a system that can be used to generate a dark soliton pulse array by using multidark soliton sources in the microring resonators and an optical multiplexer, where the different dark soliton center wavelengths can be generated. To verify the simulation results, the experimental setup was employed by using the Brillouin enhanced fiber laser in the fiber ring resonator (loop) system, where two different systems, called forward and backward schemes, were used to generate the dark soliton arrays. Three different center wavelengths of dark solitons were generated and seen to be in good agreement with the theoretical results.